Assessment of Corporate Social Responsibility Strategies by Telecommunications Companies in Federal Capital Territory, Abuja - Blessing, Attah; Akase, T. M.; Kente, J. S. (EDUMALSYS Journal of Research in Education Management, 2025)
Amid growing expectations for corporate social responsibility (CSR) in emerging markets, this study assesses CSR strategies implemented by telecommunication firms in Nigeria’s Federal Capital Territory (FCT), Abuja, and their effects on relationships with host communities. The research objective is to identify the dominant CSR practices of Globacom and 9mobile and evaluate their perceived relevance and outcomes in local communities. Using a descriptive survey design, data were gathered from respondents in FCT host communities to capture perceptions of CSR initiatives. Key findings indicate that “bonanza” promotions and discounted product sales are the most common and popular CSR strategies, followed by community building projects; additional activities include internships, sponsorship of community events and projects, and infrastructure support. While these strategies have been implemented with visible breadth, their depth and quality require enhancement; nevertheless, respondents report a notable improvement in telecom–community relations. The study concludes that CSR by the two firms is present and relationship-enhancing but uneven in strategic alignment with community needs. The contribution lies in evidencing the predominance of sales-driven CSR and underscoring implications for stakeholder engagement and policy: telecom providers should prioritize needs-based, high-quality CSR co-designed with community leaders, while policymakers should develop and enforce tailored CSR frameworks with periodic monitoring to prevent community exploitation and strengthen accountability.